Hubungan Kadar Hemoglobin Terhadap Proses Penyembuhan Luka Post Sectio Caesarea di Rumah Sakit Aura Syifa Kabupaten Kediri - Koen, Dorothy Carissa Aditya; Pratamaningtyas, Susanti; Rahayu, Dwi Estuning; Hardjito, Koekoeh (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2025)
The wound from a sectio caesarea can be at risk of infection if the healing process is compromised. Among the factors that can affect wound healing is low hemoglobin levels, which indicates the presence of anemia. This study is a quantitative observational design and prospective cohort approached. The sample was 48 respondents who were taken by consequtive sampling. Data collection was obtained from patient laboratory results and REEDA observation sheets. Data analysis was carried out using Chi Square statistical test. The results showed a p-value of 0.016 < 0.05, meaning that there is a statistical relationship hemoglobin levels and the post sectio caesarea wound healing process at Aura Syifa Hospital, Kediri Regency. It is suggested that the research site should develop procedures for monitoring hemoglobin levels in normal postpartum and post cesarean section mothers to prevent complications that can hinder the wound healing process. As well as improve education to patients about the importance of nutritional intake, especially iron and protein which aims to maintain optimal hemoglobin levels to support wound healing.